Fundamental physical testing of rattle - Design and evaluation of a rattle producing test rig - Svensson, Axel; Hasselström, Jonathan (My University, 2017)
Squeak and rattle is a cause of high warranty costs and a driver behind the production of pre-series cars for subjective evaluation. An important feature for a premium car brand is a high perceived quality and consequently the lack of squeak and rattle issues. To bring down development time and cost while still increasing the squeak and rattle capabilities, the automotive industry is now striving towards better models for virtual evaluation of squeak and rattle. This master’s thesis is a step toward virtual rattle evaluations at Volvo Car Corporation. A test rig for rattle measurement was successfully designed, built, tested and evaluated. An objective rattle metric, based on psychoacoustics theory, was evaluated by comparison of subjective clinical trial results of rattle produced by the test rig. Some features, such as temperature dependency, could be verified through the virtual evaluation of rattle with the objective metric while other features could not, judging from comparisons with the subjective data. The overall congruence between subjective and objective evaluation was inconsistent. More work is needed before any model for virtual evaluation can be used in the development of new car models. However, all hypotheses set out by the group were confirmed, if considering the mean value trends, both by the objective metric and the subjective listening clinical trials if studying the results of these independently. This means that both of the evaluation methods work well by itself but that the connection between them is yet to be established. Keywords: Squeak, Rattle, Clinical Trials, Virtual evaluation, Psychoacoustics, Physical Testing
Keywords: Produktion; Teknisk mekanik; Tillförlitlighets- och kvalitetsteknik; Production; Applied Mechanics; Reliability and Maintenance